Auroral zone dayside precipitation during magnetic storm initial phases - Tsurutani, B.T.; Zhou, X.Y.; Arballo, J.K.; Gonzalez, W.D.; Lakhina, G.S.; Vasyliunas, V.; Pickett, J.S.; Araki, T.; Yang, H.; Rostoker, G.; Hughes, T.J.; Lepping, R.P.; et al. (My University, 2001)
Significant charged-particle precipitation occurs in the dayside auroral zone during and after interplanetary shock impingements on the Earth's magnetosphere. The precipitation intensities and spatial and temporal evolution are discussed. Although the post-shock energy flux (10–Full-size image (<1 K)) is lower than that of substorms, the total energy deposition rate may be considerably greater (∼ an order of magnitude) than nightside energy rates due to the greater area of the dayside portion of the auroral oval (defined as extending from 03 MLT through noon to 21 MLT). This dayside precipitation represents direct solar wind energy input into the magnetosphere/ionosphere system. The exact mechanisms for particle energization and precipitation into the ionosphere are not known at this time. Different mechanisms are probably occurring during different portions of the storm initial phase. Immediately after shock compression of the magnetosphere, possible precipitation-related mechanisms are: (1) betatron compression of preexisting outer zone magnetospheric particles. The anisotropic plasma is unstable to loss-cone instabilities, leading to plasma wave growth, resonant particle pitch-angle scattering and electron and proton losses into the upper ionosphere. (2) The compression of the magnetosphere can also lead to enhanced field-aligned currents and the formation of dayside double-layers. Finally (3) in the latter stages of the storm initial phase, there is evidence for a long-lasting viscous-like interaction occurring on the flanks of the magnetopause. Ground-based observations identifying the types of dayside auroral forms would be extremely useful in identifying the specific solar wind energy transfer mechanisms.
Keywords: Aurora; Magnetic Storms; Magnetosphere; Magnetic storms; Auroral zone